(untitled) (Педагогіка вищої та середньої школи, 2007)
In this article is considered a problem of development of scientific and scientific-technical activity at universities of the country in a context of integration of system of higher education and the academic science. Showed the results of the analysis of foreign experience and of Russian-American cooperation within the program of integration of a science and education. Is offered forms and actions for development of a science in system of higher education on the basis of application of models of research, innovational and regional universities, university complexes and the scientific-educational centers.